Three-Dimensional Modeling of Visual Pollution of Generator Wires in Ramadi City - Sarah Abdul Ghani Ahmed , Dr. Zuhair Jaber Mushref (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Visual pollution is one of the problems of the times and its continued spread threatens the urban future of every city, so it must be addressed and appropriate solutions clarified. And visual pollution is defined as (it is every artificial human act that changes the features of the urban environment of the city and distorts the views and causes command psychological discomfort that leads to a dissonance in the components that make up the visual scene of the city, and visual pollution is a result of neglect, poor planning and design, as well as social and economic misconduct. Visual fatigue and discomfort, and it can be said that it is a product of the civilized and civil development of the era of speed).